Stb6 mediates stomatal immunity, photosynthetic functionality, and the antioxidant system during the Zymoseptoria tritici-wheat interaction - Ghiasi Noei, Fateme; Imami, Mojtaba; Didaran, Fardad; Ghanbari, Mohammad Amin; Zamani, Elham; Ebrahimi, Amin; Aliniaeifard, Sasan; Farzaneh, Mohsen; Javan-Nikkhah, Mohammad; Feechan, Angela; Mirzadi Gohari, Amir (Frontiers in Plant Science, 2022)
This study offers new perspectives on the biochemical and physiological changes that occur in wheat following a gene-for-gene interaction with the fungal pathogen Zymoseptoria tritici . The Z. tritici isolate IPO323, carries AvrStb6, while ΔAvrStb6#33, lacks AvrStb6. The wheat cultivar (cv.) Shafir, bears the corresponding resistance gene Stb6. Inoculation of cv. Shafir with these isolates results in two contrasted phenotypes, offering a unique opportunity to study the immune response caused by the recognition of AvrStb6 by Stb6. We employed a variety of methodologies to dissect the physiological and biochemical events altered in cv. Shafir, as a result of the AvrStb6-Stb6 interaction. Comparative analysis of stomatal conductance demonstrated that AvrStb6-Stb6 mediates transient stomatal closures to restrict the penetration of Zymoseptoria tritici. Tracking photosynthetic functionality through chlorophyll fluorescence imaging analysis demonstrated that AvrStb6-Stb6 retains the functionality of photosynthesis apparatus by promoting Non-Photochemical Quenching (NPQ). Furthermore, the PlantCV image analysis tool was used to compare the H2O2 accumulation and incidence of cell death (2, 4, 8, 12, 16, and 21 dpi), over Z. tritici infection. Finally, our research shows that the AvrStb6-Stb6 interaction coordinates the expression and activity of antioxidant enzymes, both enzymatic and non-enzymatic, to counteract oxidative stress. In conclusion, the Stb6-AvrStb6 interaction in the Z. tritici-wheat pathosystem triggers transient stomatal closure and maintains photosynthesis while regulating oxidative stress.